Impact of a Novel Valerian Extract on Sleep Quality, Relaxation, and GABA/Serotonin Receptor Activity in a Murine Model - Şahin, Kazım; Gencoglu, Hasan; Korkusuz, Ahmet Kayhan; Orhan, Cemal; Aldatmaz, Ismail Ertug; Erten, Fusun; Kilic, Ertugrul (Mdpi, 2024)
Insomnia is a major global health issue, highlighting the need for treatments that are both effective and safe. Valerian extract, a traditional remedy for sleep problems, offers potential therapeutic options. This research examined the potential sleep-enhancing effects of VA (Valerian Pdr%2) in mice. The study evaluated sleep quality by comparing the impact of the VA extract against melatonin on brain activity, using electrocorticography (ECoG) to assess changes in brain waves. For this purpose, the study utilized two experimental models on BALB/c mice to explore the effects of caffeine-induced insomnia and pentobarbital-induced sleep. In the first model, 25 mice were assigned to five groups to test the effects of caffeine (caffeine, 7.5 mg/kg i.p) alone, caffeine with melatonin (2 mg/kg), or caffeine with different doses of valerian extract (100 or 300 mg/kg) given orally on brain activity, assessed via electrocorticography (ECoG) and further analyses on the receptor proteins and neurotransmitters. In the second model, a different set of 25 mice were divided into five groups to examine the impact of pentobarbital (42 mg/kg) alone, with melatonin, or with the valerian extract on sleep induction, observing the effects 45 min after administration. The study found that ECoG frequencies were lower in groups treated with melatonin and two doses of valerian extract (100 and 300 mg/kg), with 300 mg/kg showing the most significant effect in reducing frequencies compared to the caffeine control group, indicating enhanced sleep quality (p < 0.05). This was supported by increased levels of serotonin, melatonin, and dopamine and higher levels of certain brain receptors in the melatonin and valerian extract groups (p < 0.05). Modulatory efficacy for the apoptotic markers in the brain was also noted (p < 0.05). Additionally, melatonin and both doses of VA increased sleep duration and reduced sleep onset time compared to the pentobarbital control, which was particularly notable with high doses. In conclusion, the findings suggest that high doses (300 mg/kg) of valerian extract enhance both the quantity and quality of sleep through the GABAergic pathway and effectively increase sleep duration while reducing the time to fall asleep in a pentobarbital-induced sleep model in mice.
Keywords: caffeine; melatonin; valerian; sleep disturbance; neurotransmitters; apoptosis